Writing the History of the Philosophy Department of Vilnius University - Plėšnys, Albinas (Problemos, 2018)
[text in Lithuanian] Review of: Kalenda, Č., 2018. Profesorius Eugenijus Meškauskas: asmenybė ir veikla. [Professor Eugenijus Meškauskas: Personality and Deeds, in Lithuanian], Vilnius: Margi raštai. –132 p. [4] iliustr. lap. – Summary in English. – Tiražas [150] egz. – ISBN 978-9986-09-486-9.